Neurorepair and Regeneration of the Brain: A Decade of Bioscaffolds and Engineered Microtissue - Zamproni, Laura N.; Mundim, Mayara T. V. V.; Porcionatto, Marimelia A. (Frontiers in Cell and Developmental Biology, 2021)
Repairing the human brain remains a challenge, despite the advances in the knowledge of inflammatory response to injuries and the discovery of adult neurogenesis. After brain injury, the hostile microenvironment and the lack of structural support for neural cell repopulation, anchoring, and synapse formation reduce successful repair chances. In the past decade, we witnessed the rise of studies regarding bioscaffolds’ use as support for neuro repair. A variety of natural and synthetic materials is available and have been used to replace damaged tissue. Bioscaffolds can assume different shapes and may or may not carry a diversity of content, such as stem cells, growth factors, exosomes, and si/miRNA that promote specific therapeutic effects and stimulate brain repair. The use of these external bioscaffolds and the creation of cell platforms provide the basis for tissue engineering. More recently, researchers were able to engineer brain organoids, neural networks, and even 3D printed neural tissue. The challenge in neural tissue engineering remains in the fabrication of scaffolds with precisely controlled topography and biochemical cues capable of directing and controlling neuronal cell fate. The purpose of this review is to highlight the existing research in the growing field of bioscaffolds’ development and neural tissue engineering. Moreover, this review also draws attention to emerging possibilities and prospects in this field.